2022
DOI: 10.1007/s12035-021-02613-5
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Rescues Memory and Improves Pathological Hallmarks in the 3xTg-AD Model of Alzheimer’s Disease

Abstract: Therapeutic strategies for Alzheimer’s disease (AD) have largely focused on the regulation of amyloid pathology while those targeting tau pathology, and inflammatory mechanisms are less explored. In this regard, drugs with multimodal and concurrent targeting of Aβ, tau, and inflammatory processes may offer advantages. Here, we investigate one such candidate drug in the triple transgenic 3xTg-AD mouse model of AD, namely the disease-modifying oral neuroimmunomodulatory therapeutic used in patients with multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 81 publications
3
17
0
Order By: Relevance
“…We have recently reported that 5xFAD mice orally treated with fingolimod have decreased activation of microglia and reactive astrocytes, decreased Aβ levels, and increased hippocampal neurogenesis 28,29 . Recently another group showed reduced phosphorylated Tau and APP levels in the brain of fingolimod treated 3xTg-AD mice 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that 5xFAD mice orally treated with fingolimod have decreased activation of microglia and reactive astrocytes, decreased Aβ levels, and increased hippocampal neurogenesis 28,29 . Recently another group showed reduced phosphorylated Tau and APP levels in the brain of fingolimod treated 3xTg-AD mice 30 .…”
Section: Discussionmentioning
confidence: 99%
“…food and drug administration. Extensive number of studies have shown its beneficial effects in murine models of neurological disorders such as MS 27 , epilepsy 53 , spinal cord injury 54 , and cerebral ischemia and Rett syndrome 21 besides those in AD [27][28][29][30] . Fingolimod actions involve the systemic immune system, which is particularly relevant in MS and the CNS where it has been shown to affect both glial 22,23 and neuronal cells 24 , and use diverse mechanisms involving cytokine production 22 , synaptic activity 55 , and anti-apoptotic functions 24 .…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in human AD patients, microglial proliferation increases in 3xTg-AD mice [28][29][30]. Therefore, CSF-1R inhibitors that suppress microglial proliferation, such as GW2580 and PLX3397, have been explored as therapeutic agents for the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a trend toward improved results in total recall test in patients who received fingolimod therapy (El Ayoubi et al, 2021). Interestingly, in a recent study, in a mouse model of Alzheimer's disease, fingolimod treatment for 12 months improved spatial working memory deficiencies; moreover, inflammation was reduced in the brain (Fagan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%